Smart agriculture monitoring system using IoT - Lashitha Vishnu Priya, P; Sai Harshith, N; N.V.K.Ramesh, Dr (International Journal of Engineering and Technology, 2018)
Atmospheric changes have been sporadic over the previous decade. Because of this in late period, atmosphere shrewd techniques called as savvy agribusiness is embraced by numerous Indian farmers. Keen farming is a robotized and coordinated data innovation executed with the Internet of Things. IOT is growing quickly and broadly connected in every remote condition. This paper presents an efficient sensor innovation and remote systems coordination of IOT innovation has been contemplated and looked into in light of the real circum-stance of agricultural activities. Real goal is to gather ongoing information of agriculture that gives simple access to the farmer. Our task screens the yield development utilizing advanced means giving the precise esteems of different parameters where upon the development depends. Additionally, it will help the farmer to screen more than one rural field in the meantime. Since, the vast majority of the observ-ing is done remotely, it will help the person to pick up data. Since, observing through our framework requires less labor, individuals with physical handicaps can be utilized for checking fields. Our task, not just tries to relieve the primitive methods identified with farming yet additionally serve the group by opening new roads for work.